Effect of steam curing regimes on temperature and humidity gradient, permeability and microstructure of concrete. (26th April 2021) - Shi, Jinyan; Liu, Baoju; Zhou, Feng; Shen, Shuai; Guo, Aofei; Xie, Youjun
Graphical abstract: Highlights: The temperature and humidity gradient during steam curing process is closely related to its long-term performance. Surface covering can significantly reduce surface porosity and damage of steam-cured concrete. The effects of steam-curing regime and surface covering method on the permeability of concrete were evaluated. The high temperature-humidity gradient during steam curing is detrimental to the development of concrete microstructure. Abstract: Steam curing has an adverse effect on the long-term performance of concrete, which is inseparable from the early hygro-thermal coupling action. The temperature-humidity field and performance of steam-cured concrete with different surface covering methods were characterized under the treatment temperature ranging from 45 to 75 ℃ by water permeability along with hydration characteristics, porosity, microhardness, and microstructure. The results show that steam-curing regimes directly affect the long-term performance of steam-cured concrete by changing internal temperature-humidity field. During the steam curing process, a higher treatment temperature often corresponds to a more complex temperature-humidity gradient, so that the steam-cured concrete exhibits low compactness and high permeability. In addition, the surface covering methods can reduce the surface porosity and interface transition zone width of steam-cured concrete. Meanwhile, with the increase of treatment temperature, the improvement effect of the surface covering methods on the impermeability of steam-cured concrete is more obvious.